2008
DOI: 10.1534/genetics.108.090126
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Sex-Independent Transmission Ratio Distortion Involving Multiple Allelic Interactions at a Single Locus in Rice

Abstract: Transmission ratio distortion (TRD) is frequently observed in inter-and intraspecific hybrids of plants, leading to a violation of Mendelian inheritance. Sex-independent TRD (si TRD) was detected in a hybrid between Asian cultivated rice and its wild ancestor. Here we examined how si TRD caused by an allelic interaction at a specific locus arose in Asian rice species. The si TRD is controlled by the S 6 locus via a mechanism in which the S 6 allele acts as a gamete eliminator, and both the male and female game… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 74 publications
6
40
0
1
Order By: Relevance
“…In contrast, no defect was observed in the pollen grains of the heterozygotes, although male gametes possessing the S 6 a allele were rarely transmitted to the next generation (Sano, 1992;Koide et al, 2008a). We have also revealed that Asian rice strains frequently harbor an additional allele (S 6 n ), which however, does not induce any preferential abortion in heterozygotes (S 6 /S 6 n and S 6 a /S 6 n ) at the S 6 locus (Koide et al, 2008a), as shown by test-cross experiments and subsequent genetic mapping using NILs that carry the genetic background of T65wx. The presence of the S 6 n allele, which modifies the effect of the S 6 allele in heterozygotic state at the S 6 locus, suggested that S 6 locus-mediated siTRD was caused by the allelic differentiation at the S 6 locus occurred during the evolution of Asian rice.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…In contrast, no defect was observed in the pollen grains of the heterozygotes, although male gametes possessing the S 6 a allele were rarely transmitted to the next generation (Sano, 1992;Koide et al, 2008a). We have also revealed that Asian rice strains frequently harbor an additional allele (S 6 n ), which however, does not induce any preferential abortion in heterozygotes (S 6 /S 6 n and S 6 a /S 6 n ) at the S 6 locus (Koide et al, 2008a), as shown by test-cross experiments and subsequent genetic mapping using NILs that carry the genetic background of T65wx. The presence of the S 6 n allele, which modifies the effect of the S 6 allele in heterozygotic state at the S 6 locus, suggested that S 6 locus-mediated siTRD was caused by the allelic differentiation at the S 6 locus occurred during the evolution of Asian rice.…”
Section: Introductionmentioning
confidence: 93%
“…NIL-S 6 carries the short arm and a portion of the long arm of chromosome 6 from Ruf-S 6 in the genetic background of T65wx (Sano, 1992;Matsubara et al, 2003;Koide et al, 2008a formally named as T65S 6 [W593]). T65wx harbors the S 6 a allele at the S 6 locus (near the centromeric region of chromosome 6), whereas Ruf-S 6 and NIL-S 6 harbor the S 6 allele at the S 6 locus (Koide et al, 2008a). Although T65wx harbors wx gene from Kinoshita-mochi (Oka, 1974; derived from BC 12 ), wx gene does not affect S 6 locus-mediated TRD.…”
Section: Genetic Stocksmentioning
confidence: 99%
See 3 more Smart Citations